2016
DOI: 10.1002/oby.21702
|View full text |Cite
|
Sign up to set email alerts
|

Randomized sham‐controlled trial evaluating efficacy and safety of endoscopic gastric plication for primary obesity: The ESSENTIAL trial

Abstract: Objective: Evaluate safety and efficacy of the pose TM procedure for obesity treatment.Methods: Subjects with Class I to II obesity were randomized (2:1) to receive active or sham procedure, after each investigator performed unblinded lead-in cases. All subjects were provided low-intensity lifestyle therapy. Efficacy end points were the mean difference in percent total body weight loss (%TBWL) at 12 months between randomized groups, and responder rate achieving 5% TBWL. The primary safety end point was inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
80
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 141 publications
(83 citation statements)
references
References 19 publications
2
80
0
1
Order By: Relevance
“…Finally, some sham controls with partial cross-over design decrease scientific validity by introducing perverse incentives. For example, in the ESSENTIAL trial, subjects were randomized to an endoscopic obesity therapy or a sham procedure, with a partial cross-over for patients initially allocated to the sham arm 23 . The only subjects eligible for the cross-over study were those who did not lose weight.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, some sham controls with partial cross-over design decrease scientific validity by introducing perverse incentives. For example, in the ESSENTIAL trial, subjects were randomized to an endoscopic obesity therapy or a sham procedure, with a partial cross-over for patients initially allocated to the sham arm 23 . The only subjects eligible for the cross-over study were those who did not lose weight.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that this adverse event can be associated with significant morbidity and cost to the healthcare system. Studies investigating novel obesity and GERD treatments report placement of large Bougies up to 54F being advanced into the esophagus and rotated at regular intervals to simulate the study intervention, device placement and maneuvering 23,33 . This carries the risk of mucosal abrasion, bleeding, aspiration, and perforation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when POSE was compared to sham procedure in the ESSENTIAL trial, mean (±SD) TBWL was reported to be only 4.95 ± 7.04% (n = 220) . These less robust findings could be attributed to a lack of lifestyle intervention in the entire study population, because the mean weight loss in the POSE group was 3.6‐fold that of the sham group . This highlights the importance of intensive lifestyle modifications in conjunction with endoscopic bariatric interventions.…”
Section: Gastric Remodeling Proceduresmentioning
confidence: 98%
“…Primary Obesity Surgery Endolumenal is another gastric remodeling procedure that uses the FDA‐approved Incisionless Operating Platform (IOP; USGI Medical, San Clemente, California) to place 11 to 13 plications in the fundus and distal body using suture anchors. It is hypothesized that these transmural plications function to reduce postprandial accommodation of the fundus to induce early satiety and cause dysmotility of the antrum to delay gastric emptying to ultimately reduce caloric intake . A study by Espinós et al demonstrated a decrease in caloric intake from 901 kcal at baseline to 473 and 574 kcal 2 and 6 months after the procedure, respectively ( P < 0.001; n = 18).…”
Section: Gastric Remodeling Proceduresmentioning
confidence: 99%